STRATEGI PENGEMBANGAN USAHA BERAS IKATAN CINTA DENGAN METODE SWOT DAN QSPM - Rahmatul Ahya; Suprapto Suprapto; Amellia Ayu Safira (Journal Of Business, Finance, and Economics (JBFE), 2022)
Rice is one of the most important commodities in the food industry sector in Indonesia, as the main source of carbohydrates. Beras Ikatan Cinta took part as one of the market players in this commodity. After two years, it was found that there was a decline in rice sales and difficulties in marketing expansion, so a research was carried out to determine the condition of the Beras Ikatan Cinta business and analyze the most suitable business development strategy for Beras Ikatan Cinta business. Data collection was obtained through a questionnaire and calculated using the IFE and EFE matrices and then processed and analyzed using the SWOT (Strength, Weakness, Opportunity, Threat) and QSPM (Quantative Strategic Planning Matrix) methods. The results of this study indicate the formation of 10 alternative business development strategies for Beras Ikatan Cinta, namely: (a) increasing production; (b) stability and professionalism of work; (c) create Quality Control standards; (d) permanent partnership with suppliers; (e) redesigning product packaging to make it more attractive; (f) improve HR performance; (g) create programs to maintain and increase customer loyalty; (h) determination of market prices in the face of competition; (i) strengtheni capital; and (j) maintaining product characteristics. Among them the most interesting and the priority to be applied is setting Quality Control standards and redesigning product packaging wich has the same TAS value of 0.62 out of a total TAS of 3.73